Information and communication technologies as an actual resource of educational activity - Marina Vladimirovna Vakulenkova (Вестник Майкопского государственного технологического университета, 2023)
Cybernation of the world, which began in the middle of the 20th century, encompassed all spheres of the life of society, becoming an essential component of the environment. Electronic technologies are used in various industries and services, including education. The implementation of the idea of e-education has contributed to the change in educational technologies, the dominant component of which are information and communication technologies. The research problem lies in the need to disclose modern information and communication technologies as an actual resource for educational activities. The purpose of the research is to substantiate the effectiveness of the use of information and communication technologies in the educational process. The research methods are analysis, synthesis, generalization, description. The basic research method is a pedagogical experiment. The research results: the concept of "information and communication technologies" has been considered, their tools have been described; the advantages of using information and communication technologies in educational activities in the direction of training 44.03.02 Psychology and Pedagogy of primary education have been disclosed; the efficiency has been substantiated and the possibilities of using informatization means in the educational process on the basis of the branch of FSBEI HE "Adyghe State University" in the city of Belorechensk have been determined; examples of the use of information and communication technologies in the educational process in the disciplines "Modern information technologies", "Information and communication technologies in education" have been given; the results of experimental work have been presented, that confirm the increase in the efficiency of the quality of knowledge. Key conclusions: information and communication technologies include the integration of methodological techniques, technological processes, software and hardware that interact with each other in the process of using information for a specific purpose, determined by the interests of its consumers; the advantages of information and communication technologies in educational activities are the expansion of the possibilities of the educational process, the development of positive educational motivation and interest of students, an increase in the quality of knowledge, etc.